A practical comparison between the methods of determining the focal length of a convex lens - A. Kathum Al-musawi, Thill (University of Thi-Qar Journal of Science, 2017)
This study was conducted to determine the best method for determining the focal length of the lens of the lens, and the effect of the value of the thickness of the lens and the focal length in determining the type of method to be followed in the laboratories of optics to obtain the most accurate values ​​and the easiest and fastest. Three methods were chosen to determine the focal dimension, the most used methods in this laboratory, and several convex lenses (with different focal lengths) were used with each method. The software used in its version (R2013a) was used to draw and represent the data.